Relationship of Mother’s Knowledge and Family Support with Basic Immunization Completeness of 12-24 Months Children in the Covid-19 Pandemic Era in UPTD Puskesmas Cibuaya, Karawang - Fadil Fadil; Depi Lukitasari; Oktarian Pratama (Universitas Pendidikan Indonesia, 2022)
Background: Mother's knowledge and family support of immunization completeness is needed so that children get basic immunizations and as an initial step to preventing disease, especially during the Covid-19 pandemic. During the Covid-19 pandemic, the coverage of basic immunization in 2021 at the UPTD Puskesmas Cibuaya, Karawang decreased to 50.4%. The purpose of the study was to analyze the relationship between mother's knowledge and family support with the completeness of basic immunization of children aged 12-24 months during the Covid-19 pandemic era at the UPTD Puskesmas Cibuaya, Karawang.Methods: This study using a quantitative method with a cross-sectional approach. The subjects of this study were 91 mothers and families who have children aged 12-24 months. The research instrument used a questionnaire. Data were analyzed using Chi-Square test.Result: The respondents of this study were mothers aged 19-29 years (50.5%), had children aged 12-21 months (81.3%), and housewives (100%). Respondents who have good knowledge were 48 mothers (52.7%), and the rest, 43 mothers (47.3%) were not good enough. Respondents who received family support were 41 people (45.1%), while families who did not support were 50 respondents (54.9%). Respondents who gave complete immunization to their children were 47 mothers (51.6 %), while those who did not complete immunizations were 44 (48.4%) respondents. There was a relationship between mother's knowledge anthe d immunization with p-value (sig) = 0.002 0.05. There was no relationship between family support and basic immunization completeness (p-value= 0.234, p0.05). Suggestions to all relevant parties of this topic to implement programs on knowledge improvement of mothers and the community about the importance of complete basic immunization.